Spanish and Italian songbooks - Wolf, Hugo. 1860-1903 (Dover publications, 1989)
This volume contains two of the composer´s most celebrated song collections. The Spanisches Liederbuch of 44 songs -largely religious or erotic-- consists of settings of translations from Cervantes, Lope de Vega and others.